MODEL PILIHAN PENUMPANG ANGKUTAN KOTA DAN KERETA REL LISTRIK DI JAKARTA - Mezky Matthew Yandito; Alvinsyah . (Jurnal Transportasi, 2019)
Abstract With the operation of the Electric Rail Train in the Jakarta Kota-Tanjung Priok route at the end of 2015, it is estimated that there is a potential for the transfer of passengers from other modes to the Electric Rail Train. The purpose of this study is to estimate the factors that influence passenger preferences in traveling on the Jakarta Kota-Tanjung Priok route and form a demand analysis tool in the form of a modal choice model. The analysis was carried out using the binomial logit model approach which was developed based on the stated preference survey results on public transportation passengers that traveled on the similar route as the route where the Electric Rail Train operates. The factors included in the stated preference survey were obtained through literature studies and interviews, and through a pilot survey 3 factors were chosen which most influenced the mode choice. Based on the results of the correlation test, it was found that the variable that most influences the mode choice is the tariff. Keywords: passenger preferences, choice model, stated preference, tariff  Abstrak Dengan beroperasinya Kereta Rel Listrik rute Jakarta Kota–Tanjung Priok pada akhir tahun 2015, diperkirakan terdapat potensi perpindahan penumpang dari moda lainnya ke Kereta Rel Listrik. Tujuan penelitian ini adalah untuk memperkirakan faktor-faktor yang memengaruhi preferensi penumpang dalam melakukan perjalanan di rute Jakarta Kota–Tanjung Priok dan membentuk perangkat analisis permintaan berbentuk model pemilihan moda. Analisis dilakukan dengan menggunakan pendekatan model logit binomial yang dikembangkan berdasarkan hasil survei stated preference terhadap penumpang angkot yang melalui rute yang sama dengan rute Kereta Rel Listrik. Faktor-faktor yang dimasukkan dalam survei stated preference diperoleh melalui studi literatur dan wawancara, dan melalui survei pilot dipilih 3 faktor yang dinilai paling memengaruhi pilihan moda. Berdasarkan hasil uji korelasi ditemukan bahwa variabel yang paling berpengaruh terhadap pilihan moda adalah tarif. Kata-kata kunci: preferensi penumpang, model pemilihan, stated preference, tarif